NIL10: A New IL10-Receptor Binding Nanoparticle That Induces Cardiac Protection in Mice and Pigs Subjected to Acute Myocardial Infarction through STAT3/NF-κB Activation - Laura Tesoro; Ignacio Hernández; Rafael Ramírez-Carracedo; Javier Díez-Mata; Nunzio Alcharani; Beatriz Jiménez-Guirado; Karina Ovejero-Paredes; Marco Filice; Jose Luis Zamorano; Marta Saura; Carlos Zaragoza; Laura Botana (MDPI AG, 2022)
(1) Background: Early response after acute myocardial infarction (AMI) prevents extensive cardiac necrosis, in which inflammation resolution, including expression of anti-inflammatory interleukin-10 (IL-10), may play a key role. (2) Methods: We synthesized NIL10, a micelle-based nanoparticle, to target IL-10 receptor in mice and pigs subjected to AMI. (3) Results: Administration of NIL10 induced cardiac protection of wild-type and IL-10 knockout mice and pigs subjected to AMI. Cardiac protection was not induced in IL-10-receptor null mice, as shown by a significant recovery of cardiac function, in which inflammatory foci and fibrosis were strongly reduced, together with the finding that resolving M2-like macrophage populations were increased after day 3 of reperfusion. In addition, anti-inflammatory cytokines, including IL-4, IL-7, IL-10, IL-13, IL-16, and IL-27 were also elevated. Mechanistically, NIL10 induced activation of the IL-10 receptor/STAT-3 signaling pathway, and STAT3-dependent inhibition of nuclear translocation of pro-inflammatory NF-ĸB transcription factor. (4) Conclusions: Taken together, we propose using NIL10 as a novel therapeutic tool against AMI-induced cardiac damage.